Analisis Faktor Internal dan Faktor Eksternal Terhadap Pertumbuhan Aset - Riskahayu Hermayanti; Erma Setiawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to determine the analysis of internal factors and external factors to asset growth. This study uses a quantitative approach, using secondary data. The population used in this study is mining companies listed on the Indonesia Stock Exchange (IDX) for the period 2019-2023. Sampling technique in this study using purposive sampling method. For the calculation of data analysis using multiple linear regression test. As for the program used is with SPSS. The results showed that the debt to equity ratio, the size of the company and inflation do not affect the growth of corporate assets, while the return on assets affect the growth of corporate assets.